Topological and Multi-Topological Frames in the Context of Intuitionistic Modal Logic - Witczak, Tomasz (Bulletin of the Section of Logic, 2019)
We present three examples of topological semantics for intuitionistic modal logic with one modal operator □. We show that it is possible to treat neighborhood models, introduced earlier, as topological or multi-topological. From the neighborhood point of view, our method is based on differences between properties of minimal and maximal neighborhoods. Also we propose transformation of multitopological spaces into the neighborhood structures.